2023
DOI: 10.1186/s13223-022-00753-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of probiotic supplementation in patients with asthma: a randomized, double-blind, placebo-controlled trial

Abstract: Background Asthma is considered to be a chronic inflammatory disorder of the airways. Probiotics are living microorganisms that are found in the human gut and have protective effects against a wide range of diseases such as allergies. The aim of this study was to investigate the improvement of clinical asthma symptoms and changes in the expression pattern of selective microRNAs in patients with asthma and the changes in IL-4 and IFN-γ plasma levels after receiving probiotics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Previous studies have shown an association between Lactobacillus administration and immune regulation of Th1/Th2 response, reducing allergic inflammation characteristic of asthma (14,28).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have shown an association between Lactobacillus administration and immune regulation of Th1/Th2 response, reducing allergic inflammation characteristic of asthma (14,28).…”
Section: Discussionmentioning
confidence: 97%
“…This change may have been due to the significant uptick in serum SCFAs which traveled through systemic circulation and reduced inflammation in the lungs. Previous studies have shown an association between Lactobacillus administration and immune regulation of Th1/Th2 response, reducing allergic inflammation characteristic of asthma (14, 28). The effect of the herbal extracts can also not be discounted, as turmeric, holy basil, and vasaka have antioxidant and anti-inflammatory properties (18, 29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cell responses have a prominent role in immunity against COVID-19 as well as the progression of this disease. Interestingly, evidence on COVID-19 has shown that dysfunction or excessive immune response can contribute to the creation of cytokine storms, leading to rising in inflammatory mediators including IL-6, IL-8, MIP-1A, GM-CSF, and IFN-γ which caused massive damage to the respiratory system and tissue to break down [ 7 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…93 Supplementation with a probiotic mixture of multiple Lactobacilli, B. longum, and Streptococcus thermophilus in adults with asthma resulted in an improvement of lung function, a reduction in several inflammatory markers and an increase in regulatory markers. [94][95][96] However, in longitudinal studies, supplementation with L. reuteri, L. rhamnosus, or B. lactis or a mix of Lactobacilli and Bifidobacteria to pregnant women in the last month of pregnancy, 3-6 months postpartum, and after birth to their newborns till 6 months to 2 years of age did not induce a difference in asthma incidence at school age. [97][98][99][100] In conclusion, the in vivo interventions described above only seem to influence asthma symptoms in children above 3 years and adults and do not prevent asthma development, when given during pregnancy and in newborns.…”
Section: Interventi On S Tud Ie Smentioning
confidence: 93%